HEDONISME DALAM NOVEL ANTOLOGI RASA KARYA IKA NATASSA - Cahyani, Vera Intan; Nurizzati, Nurizzati (Universitas Negeri Padang, 2019)
The problem formulation in this research is how hedonism in novel Antologi Rasa by Ika Natassa is. The purpose of this study were (1) describes the form of behavior of hedonism in the novel Antologi Rasa by Ika Natassa; (2) to describe the cause of hedonism behavior in the novel Antologi Rasa by Ika Natassa; and (3) describe the impac of hedonism behavior in novel Antologi Rasa by Ika Natassa. The data of this study are the story elements of the novelÂ Antologi Rasa by Ika Natassa. The data source for this study is the novel Antologi Rasa by Ika Natassa. There are four stages to collecting data. First , read the novelÂ Antologi Rasa by Ika Natassa. Second, do library research. Third, look for and record data related to research problems. The result of this observation to express form of characterist behavior hedonism, the cause of hedonism and the impact of hedonism behavior.Â Keywords: hedonism, novel, popular literature